Association of diabetes and hypertension with elderly skin changes - Paliwal, Gaurav; Koti, Venkatarao; Dutt, Shobhit (International Journal of Research in Dermatology, 2019)
Background: The skin is the largest organ of the human body that fulfils multiple essential tasks. It forms the boundary between the inside and outside. It provides protection against mechanical and chemical threats, it provides innate and adaptive immune defences, it enables thermoregulation and vitamin D production, and it acts as the sensory organ of touch. Aging population is susceptible to many cutaneous and systemic diseases, simultaneously leading to impairment of quality of life in them. Methods: A cross sectional study was carried on patients above 60 years of age who visited the dermatology OPD at rural tertiary care centre from November 2016 to May 2017. Results: Total 540 geriatric patients with dermatosis were registered under the study, of these 203 patients had one or more systemic diseases. Hypertension (70.9%) was the commonest disease, followed by diabetes (32.5%). Conclusions: Skin diseases cause considerable morbidity in elderly, particularly if associated with other comorbid conditions, so health promotion and education can do much to reduce the risk.